A New Class of Task-Specific Imidazolium Salts and Ionic Liquids and Their Corresponding Transition-Metal Complexes for Immobilization on Electrochemically Active Surfaces - Seidl, Vera; Romero Cordero, Angel Heriberto; Heinemann, Frank Wilhelm; Scheurer, Andreas; Vogel, Carola; Unruh, Tobias; Wasserscheid, Peter; Meyer, Karsten (Chemistry - A European Journal, 2022)
Adding to the versatile class of ionic liquids, we report the detailed structure and property analysis of a new class of asymmetrically substituted imidazolium salts, offering interesting thermal characteristics, such as liquid crystalline behavior, polymorphism or glass transitions. A scalable general synthetic procedure for N-polyaryl-N’-alkyl-functionalized imidazolium salts with para-substituted linker (L) moieties at the aryl chain, namely [LPhmImHR]+ (L=Br, CN, SMe, CO2Et, OH; m=2, 3; R=C12, PEGn; n=2, 3, 4), was developed. These imidazolium salts were studied by single-crystal X-ray diffraction (SC-XRD), NMR spectroscopy and thermochemical methods (DSC, TGA). Furthermore, these imidazolium salts were used as N-heterocyclic carbene (NHC) ligand precursors for mononuclear, first-row transition metal complexes (MnII, FeII, CoII, NiII, ZnII, CuI, AgI, AuI) and for the dinuclear Ti-supported Fe-NHC complex [(OPy)2Ti(OPh2ImC12)2(FeI2)] (OPy=pyridin-2-ylmethanolate). The complexes were studied concerning their structural and magnetic behavior via multi-nuclear NMR spectroscopy, SC-XRD analyses, variable temperature and field-dependent (VT-VF) SQUID magnetization methods, X-band EPR spectroscopy and, where appropriate, zero-field 57Fe Mössbauer spectroscopy.
CRIS-Team Scopus Importer:2022-03-25
Keywords: carbene ligands; electronic structure; ionic liquids; solid-state structure; thermal properties

Bis-polyethylene glycol-functionalized imidazolium ionic liquids: A multi-method approach towards bulk and surface properties - Seidl, Vera; Bosch, Michael; Paap, Ulrike; Livraghi, Mattia; Zhai, Ziwen; Wick, Christian; Koller, Thomas Manfred; Wasserscheid, Peter; Maier, Florian; Smith, Ana-Suncana; Bachmann, Julien; Steinrück, Hans-Peter; et al. (Journal of Ionic Liquids, 2022)
Adding to the versatile class of ionic liquids, we report a new series of hydrophilic polyethylene glycol-functionalized room-temperature ionic liquids, offering interesting thermo- and electrochemical behavior as well as remarkable surface properties. A scalable and generally applicable synthetic procedure for the preparation of N,N’-bis(polyethylene glycol)imidazolium salts, generally abbreviated as [(mPEGn)2Im][A] (n = 2‒6, A = I‒, OMs‒, PF6‒, NTf2‒) was developed. These ionic liquids were studied concerning their thermo- and electrochemical properties, such as phase transition behavior, decomposition temperature, viscosity, and density, as well as electrical conductivity and electrochemical stability, using i.a. differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV). Additionally, the surface properties were investigated by angle-resolved X-ray photoelectron spectroscopy (ARXPS) and the pendant drop method. olecular dynamics simulations complement the studies and provide insight into the molecular structure of the ionic liquids and their specific orientation at the liquid-vacuum interface.<br

Direct Correlation of Surface Tension and Surface Composition of Ionic Liquid Mixtures—A Combined Vacuum Pendant Drop and Angle-Resolved X-ray Photoelectron Spectroscopy Study - Paap, Ulrike; Seidl, Vera; Meyer, Karsten; Maier, Florian; Steinrück, Hans-Peter (Molecules, 2022)
We investigated the surface tension and surface composition of various mixtures of the two ionic liquids (ILs) 1-methyl-3-octyl-imidazolium hexafluorophosphate [C8C1Im][PF6] and 1,3-bis(polyethylene glycol)imidazolium iodide [(mPEG2)2Im]I in the temperature range from 230 to 370 K under ultraclean vacuum conditions. The surface tension was measured using a newly developed apparatus, and the surface composition was determined by angle-resolved X-ray photoelectron spectroscopy (ARXPS). In the pure ILs, the alkyl chains of [C8C1Im][PF6] and the PEG chains of [(mPEG2)2Im]I are enriched at the IL/vacuum interface. In the mixtures, a strong selective surface enrichment of the alkyl chains occurs, which is most pronounced at low [C8C1Im][PF6] contents. For the surface tension, strong deviations from an ideal mixing behaviour take place. By applying a simple approach based on the surface composition of the mixtures as deduced from ARXPS, we are able to predict and reproduce the experimentally measured temperature-dependent surface tension values with astonishingly high accuracy.
CRIS-Team Scopus Importer:2022-12-23
Keywords: angle-resolved X-ray photoelectron spectroscopy (ARXPS); ionic liquids; pendant drop (PD); surface composition; surface tension; ultra-high vacuum (UHV)

Thermochemical and Structural Studies of New Chiral and Achiral Long Alkyl Chain Functionalized Imidazolinium Ionic Liquids - Seidl, Vera; Sternberg, Michelle; Heinemann, Frank Wilhelm; Schmiele, Martin; Unruh, Tobias; Wasserscheid, Peter; Meyer, Karsten (Crystal Growth and Design, 2021)
Adding to the versatile class of ionic liquids (ILs), an entirely new series of imidazolinium-based ionic liquids is reported herein, offering chirality and important thermal characteristics, such as polymorphism, glass transition, and plastic crystalline behavior. An efficient and general procedure for the preparation of long N,N′-alkyl chain-substituted compounds with either saturated (s) or chiral (c) cyclohexyl (cyC6)-substituted imidazolium (Im) backbones, namely, [C12C12RsIm][A] (A = Br-, [BF4]-, [ClO4]-, [PF6]- R = H, Me, iPr) and [C12C12cIm-cyC6][A] (A = Br-, I-, [I3]-, [BF4]-, [ClO4]-, [PF6]-, [SbF6]-, [BPh4]-), was developed, and the novel compounds were studied by thermochemical methods (DSC, TGA), X-ray diffraction in the small angle regime (SAXS), single-crystal X-ray diffraction (SC-XRD), and specific rotation analysis.
CRIS-Team Scopus Importer:2021-10-29